Essentials in robotics - Wilson, Rowland (Clanrye International, 2015)
This book of robotic science discusses topics through researches and case studies from numerous scientists, researchers and engineers from across the globe. It describes the computational techniques for a robot's programming and also provides a wide approach about hardware construction. This book is assembled in such a manner, that it will provide in-depth knowledge about the theory and practices of robotics. Topics covered in this book include applications of robotics to different fields of science such as in space engineering, medical sciences, nuclear science, and computer engineering.